Strengthening the Position and Function of Nazhir Waqf as an Independent Institution - faisal faisal (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. Nazhir's position as an independent waqf institution is very important and central because the party who receives the waqf property from the wakif to be managed and developed according to its designation is called nazhir and does not depend on any party. Specifically in the Waqf Law, there is no article that specifically explains the position of Nazhir. Nazhir individuals, organizations and legal entities have a very important position in terms of their duties and responsibilities, in maintaining and empowering waqf assets so that they can develop so that the value of the benefits (profits) obtained can be used for social interests, especially for Muslims. The importance of Nazhir's position in the context of waqf is as a party who has the responsibility to maintain, maintain, manage and develop waqf assets, but in terms of waqf fiqh, in the view of the scholars, in principle Nazhir is not included in one of the pillars of waqf.